Molecular characterization of Babesia peircei and Babesia ugwidiensis provides insight into the evolution and host specificity of avian piroplasmids. Issue 3 (December 2017) - Yabsley, Michael J.; Vanstreels, Ralph E.T.; Shock, Barbara C.; Purdee, Michaelle; Horne, Elizabeth C.; Peirce, Michael A.; Parsons, Nola J.
Abstract: There are 16 recognized species of avian-infecting Babesia spp. (Piroplasmida: Babesiidae). While the classification of piroplasmids has been historically based on morphological differences, geographic isolation and presumed host and/or vector specificities, recent studies employing gene sequence analysis have provided insight into their phylogenetic relationships and host distribution and specificity. In this study, we analyzed the sequences of the 18S rRNA gene and ITS-1 and ITS-2 regions of two Babesia species from South African seabirds: Babesia peircei from African penguins ( Spheniscus demersus ) and Babesia ugwidiensis from Bank and Cape cormorants ( Phalacrocorax neglectus and P. capensis, respectively). Our results show that avian Babesia spp. are not monophyletic, with at least three distinct phylogenetic groups. B. peircei and B. ugwidiensis are closely related, and fall within the same phylogenetic group as B. ardeae (from herons Ardea cinerea ), B. poelea (from boobies Sula spp.) and B. uriae (from murres Uria aalge ). The validity of B. peircei and B. ugwidiensis as separate species is corroborated by both morphological and genetic evidence. On the other hand, our results indicate that B. poelea might be a synonym of B. peircei, which in turn would be a host generalist that infects seabirds from multiple orders. Further studies combining morphological and molecular methods are warranted to clarify the taxonomy, phylogeny and host distribution of avian piroplasmids. Graphical abstract: Image 1 Highlights: Babesia peircei ( Bp ) infects penguins and B. ugwidiensis ( Bu ) infects cormorants. Gene sequences of Bp and Bu were analyzed from birds sampled in South Africa. Phylogenetic analysis reveals at least three paraphyletic groups of avian Babesia. Bp and Bu form a phylogenetic group along with other Babesia from aquatic birds. Avian Babesia might not be host-specific at the order level as previously thought.